Micro-climatic Assessment and Thermal Time Requirement in Relation to Datepalm Fruit Maturity in Arid Rajasthan - Singh, R S; Vashistha, B B; Prasad, R N (Annals of Arid Zone, 2016)
Micro-climatic changes inside the irrigated datepalm (Phoenix dactylifera) orchard of 14 to l8-y(’ar-old plantation with 8 x 8 metre spacing were studied during three consecutive years, 1993-95, at CR Farm, Jodhpur. The change in micro-climate of the orchard is mainly due to dropping of air temperature, decrease in saturated vapour pressure deficit (SVPD) by 2 to 5 mb and reduction in wind speed compared to that outside the orchard. This indicated the possibility of growing summer and rainy season vegetable crops inside the orchard. Relationships between onset of various phenological growth stages in three promising cultivars of datepalm (viz: Halawy. Shamran and Zahidi) and ambient temperature were also worked out. It is found that the datepalm fruit required 2304 to 2601 Â°Cd heat unit to reach at doka maturity stage after spathe emergence. However, dang maturity stage required heat unit about 2769 to 2879Â°Cd. which is normally not possible under Jodhpur condition before the start of rainy season.